89.3k views
0 votes
3(1 - 3x) = 2(- 4x + 7) solve

User Tami
by
4.7k points

2 Answers

6 votes

3(1 - 3x) = 2(- 4x + 7)

multiply the first bracket by 3

(3)(1)=3x

(3)(-3x)=9x

multiply the second bracket by 2

(2)(-4x)=8x

(2)(7)=14

3-9x=-8x+14

move -8x to the other side

sign changes from -8x to +8x

3-9x+8x=-9x+8x+14

3-x=14

move 3 to the other side

3-3-x=14-3

-x=11

multiply both sides by -1 to get +x

(-1)(-x)=x

(-1)(11)=-11

Answer:

x=-11

User Neodymium
by
4.9k points
1 vote

Answer:

x=-11

Explanation:

3(1-3x)=2(-4x+7)

1) Distribute 3 to 1 and -3x:

3-9x=2(-4x+7)

2) Distribute 2 to -4x and 7:

3-9x=-8x+14

3) Subtract 3 from both sides::

-9x=-8x+11

4) Add 8x to both sides:

-1x=11

5) Divide both sides by -1:

x=-11

Footnotes:

-The Distributive property says a(b+c)=ab+ac

-When you have a negative variable, there is an implied (-1) before the variable :)

User YotamN
by
5.2k points